Analisis Penggunaan Earbuds atau Earphone di Telinga Saat Berkendara Roda Dua - Inderawati, Maria Magdalena Wahyuni; Mahealani, Sefanya; Gracia, Marsela (Metris: Jurnal Sains dan Teknologi, 2025)
Using earphones or earbuds while driving positively and negatively impacts the driver. Congestion is a condition that causes motorists to use these hearing aids. However, the use of hearing aids while driving can threaten the safety of drivers and other drivers. The Bumi Serpong Damai (BSD) area is an area with many motorcyclists, so it can be a reference for motorists to pay attention to the dangers of using earphones while driving. Using earphones while driving, motorcyclists often do not focus on road conditions. Moreover, motorists can be indifferent to signs and other motorists. Therefore, a study was conducted on the use of hearing aids by two-wheeled riders in the BSD area to reveal the underlying problems associated with the use of hearing aids when driving. This study was conducted through the distribution of questionnaires and data processing using the chi-square test and logistic regression. This study aimed to determine motorcyclists’ level of awareness about the dangers of using earphones while driving. The result showed that a relationship exists between the frequency of use and driving comfort; the dominant factor affected by using hearing aids while driving is a reduction in emotions due to traffic jams. This study recommends that the government address traffic congestion due to its strong impact on driver emotions. For motorcyclists, it is advised to keep the earphone volume low to maintain focus on traffic signs and surrounding sounds.